A new look at effective interactions between microgel particles - Maxime J. Bergman (Nature Portfolio, 2018)
Changing temperature of thermoresponsive microgels is typically used as a proxy for modifying volume fraction based on the assumption that doing so does not alter the interaction potential. Bergman et al. shows that this picture is oversimplified and microgels are better described by a multi-Hertzian model.